Mapping the Language of Male Partner Violence: An Historical Examination of Power, Meaning, and Ambivalence - Wolff, Christina (Violence against women, 2023)
This article questions why violence carried out by men toward their female romantic partners remains so prevalent today by examining how it has been understood and talked about over time. The aim here is twofold: the first is to historically map the changes in how male partner violence has been addressed in society—and to what effect. The second is to examine subtle dynamics within this historical map in order to suggest how language could be used to destabilize its fixture in society.